Exploration of Marine Tourism Development Based on Local Community Empowerment in Kuranji Dalang Village, Labuapi District, West Lombok Regency - I Ketut Antara; Fransisco Dei Graciano Gadu; An Nuur Khairune Nisa; Willy Susanto; Inti Pranawati; Gina Gartiwi PR (Jurnal Toursci, 2026)
Background. The development of marine tourism is one of the strategic tourism sectors in the development of coastal areas because it has significant economic, social, and ecological potential. Coastal ecosystems are transitional areas between land and ocean that have high biodiversity and important ecological functions. In the tourism sector. Kuranji Dalang Village in Labuapi District, West Lombok Regency has coastal resources that have the potential to be developed as a community-based marine tourism destination. Purpose. This research aims to identify tourist attractions, explore the potential of marine tourism in Kuranji Village, the impact of marine tourism development, and inhibiting factors in the development of marine tourism based on community empowerment in Kuranji Village. Method. The method used in this study is a qualitative descriptive approach through field observations, interviews with the community and members of the Tourism Awareness Group (Pokdarwis), and local MSMEs. Results. The results of the study show that Kuranji Dalang Village has various marine tourism attractions, including culinary attractions, camping areas, recreational fishing attractions, beach panoramas with the golden sunset phenomenon. Conclusion. The development of community-based marine tourism in this village can be carried out through the empowerment of local communities through creative economy management, strengthening of Human Resources (HR) of local communities, optimizing marketing and promotion of marine tourist destinations.